2019
DOI: 10.1111/1467-8454.12164
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility and strategic trade policy: An endogenous timing game and its policy implications

Abstract: This study incorporates the corporate social responsibility (CSR) initiatives of a domestic firm and analyzes strategic trade policy toward a foreign firm in a different market structure. We show that the tariff rate under a foreign (domestic) firm's leadership is lowest when the degree of CSR is large (small). We also show that the foreign firm's leadership yields the highest welfare when the degree of CSR is intermediate, while the domestic firm's leadership yields the highest welfare otherwise. In an endoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…15 See, among others, Wang and Chen (2011), Xu (2018), andCho et al (2019). 16 As we discussed after presenting Proposition 1, if κ 0 is close to zero, each private firm's profit can increase with n, regardless of κ.…”
Section: Free-entry Marketmentioning
confidence: 98%
“…15 See, among others, Wang and Chen (2011), Xu (2018), andCho et al (2019). 16 As we discussed after presenting Proposition 1, if κ 0 is close to zero, each private firm's profit can increase with n, regardless of κ.…”
Section: Free-entry Marketmentioning
confidence: 98%
“…L. F. S. Wang et al (2012) assume that the products in the market come from foreign firms, while Y. M. Chang et al (2014) assume that a domestic firm competes with a foreign firm in the market. Cho et al (2019) showed that the tariff rate under a foreign (domestic) firm's Stackelberg leadership is lowest when the degree of CSR is large (small).…”
Section: Introductionmentioning
confidence: 99%
“…Cho et al. (2019) showed that the tariff rate under a foreign (domestic) firm's Stackelberg leadership is lowest when the degree of CSR is large (small).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Pal (1998) and Amir and De Feo (2007) extended the study to the case of a mixed oligopolistic market. Lu (2006) and Cho et al (2019) studied the case of international competition. Baťrcena-Ruiz (2007), Matsumura and Ogawa (2014), and Lee and Xu (2018) considered endogenous timing decisions under price competition.…”
Section: Introductionmentioning
confidence: 99%